The Impact of Entrepreneurial Education on Entrepreneurial Intention through Self-Efficacy - Boby Lianto; Chritina Whidya Utami; Wirawan Dwi Radianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Entrepreneurial education is recognized as a catalyst for entrepreneurial intention, but inconsistent empirical evidence underscores the importance of examining psychological mediators such as self-efficacy to clarify its impact. This research examined how entrepreneurial education affects entrepreneurial intentions among university students in East Nusa Tenggara, Indonesia. This study investigated both direct influences and indirect effects through self-efficacy using the Theory of Reasoned Action. Survey data from 211 students across five institutions revealed a significant dual pathway. The measurement model showed excellent reliability with all constructs exceeding recommended thresholds, though discriminant validity concerns between self-efficacy and other constructs suggest potential conceptual overlap in this cultural context. Entrepreneurial education showed a modest direct effect on intentions, yet demonstrated a much stronger indirect impact through self-efficacy. The findings indicated entrepreneurial education substantially enhances self-efficacy, which then strongly influences entrepreneurial intentions. With a considerable total effect of 0.756, our results highlight that nearly 79% of entrepreneurial education’s impact occurs through self-efficacy enhancement rather than direct knowledge acquisition. These findings extend entrepreneurship theory by clarifying how educational interventions work through psychological mechanisms. For educators and policymakers in developing regions, this study emphasizes balancing knowledge transfer with self-efficacy development to maximize entrepreneurial outcomes.